Corrosion sensor for monitoring reinforced concrete structures: Tests on reinforced concrete specimens - Calvo Valdés, Analiet; F. Medeiros, Marcelo H.; Macioski, Gustavo (Revista ALCONPAT, 2021)
The aim of the research was to evaluate the effectiveness of a galvanic multi-electrode sensor to detect the probability of corrosion in reinforced concrete prisms subjected to drying and wetting cycles in a NaCl solution. The corrosion potential (Ecorr) readings obtained using a copper sulfate copper electrode (Cu/CuSO4) were analyzed along with the galvanic current (Igal) and galvanic potential (Epar) readings. The sensor developed showed sensitivity to detect the chloride front and to predict the possibility of corrosion of the reinforcement. The parameters Ecorr, Epar and Igal presented distinct behaviors in terms of its use as parameters for corrosion monitoring.